শহীদ বুদ্ধিজীবী মোফাজ্জল হায়দার চৌধুরীর একাত্তরের ডায়েরি - মওদুদ, বেবি
Correspondece collection of some martyrs and freedom fighters of the 1971 independence revolution in Bangladesh, written at the time of the revolution.